PC Tools Deluxe™ : the complete reference. - Bender, Hy (Osborne McGraw-Hill, 1990)
"Hy Bender's new complete reference guide gives you a fast start with PC tools Deluxe versión 6 and a thorough. Wll organized and clearly written to help you get the most from our hardware. Through step-by-step instructions. PC Tools Deluxe™: the complete reference helps you quickly learn the fundamentals of this outstanding DOS-based program, including how to • Back up and restore your hard disk. • Recover deleted files. • Recover formated disks. • Repair detective disks." (Copied from the paste).